HUBUNGAN PENDEKATAN LINGKUNGAN ALAM SEKITAR (PLAS) DENGAN HASIL BELAJAR SISWA KELAS V SEKOLAH DASAR - Suprapto, Hidayah Mulyaningsih (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2019)
This study aims to determine the relationship between the approach of the natural environment with the learning outcomes of students in grade V SD N 3 Klaten Grabag Magelang. The learning that is happening now has increased material that is taught increasingly difficult how to teach teachers is still conventional lack of media and facilities learning especially in natural science learning that requires concrete understanding.  For this reason teachers need to innovate in learning one of them using the natural environment approach that can be used in science subjects.  The subjects of this study were students of grade V SD N 3 Klaten as many as 32 children 16 children of the experimental group and 16 control groups selected by the object random sampling system in this study were natural science learning outcomes using a natural environment approach around data collection techniques used in the form of observation and documentation. this type of research is a quasi-experimental with pretest posttest control group design research method used is quantitative data analysis techniques in this study using t test with a significance level of 5%. The results of the study showed that the experimental group obtained the calculated thitung (7,580) > t tabel(df:15) (2,145),  and the p (0,000) < dari 0,05 value with the results of the study meant that there was an increase in student learning outcomes in grade V SD N 3 Klaten using a significant natural environment approach to student learning outcomes so that it could be concluded that there was a significant relationship between the approaches  the surrounding natural environment with student learning outcomes in the material Adjustment of living things with the environment in grade V SD Negeri 3 Klaten Grabag Magelang.